The myth of the open encyclopedia.: Centuria, a time-bomb (meta)fiction (ENTHYMEMA, 2024)
Centuria, Giorgio Manganelli’s metafictional novel published in 1979 is an open encyclopaedia (in the words of Italo Calvino), a textual structure which springs both from an epistemological skepticism and a more problematic compositional strategy of literary creation. The open encyclopaedia is built on the balance between two opposing forces: a centrifugal force, that unleashes an endless proliferation of stories; and a centripetal force, which organize them within a structure. The main purpose of this essay is to examine in detail these two opposite poles, focusing first on the connection between Centuria and reference books (such as dictionary or encyclopaedia); then on the detection of particular ‘pluralization mechanisms’ including: the re-use of previous narrative material, the frequent hypothetical and conjectural speech, the potential facet of narrated events, lastly the reoccurrence of three crucial and meaningful concepts, namely the list, the scheme and the catalogue.
Keywords: Italian Literature; Giorgio Manganelli; metafictional; plurality